2021
DOI: 10.1530/erc-21-0092
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic and hormonal remodeling of colorectal cancer cell signaling by diabetes

Abstract: The existence of molecular links that facilitate colorectal cancer (CRC) development in the population with type 2 diabetes (T2D) is supported by substantial epidemiological evidence. This review summarizes how the systemic metabolic and hormonal imbalances from T2D alter CRC cell metabolism, signaling and gene expression as well as their reciprocal meshing, with an overview of CRC molecular subtypes and animal models to study the diabetes-CRC cancer links. Metabolic and growth factor checkpoints ensure a phys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
11
0
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 77 publications
2
11
0
4
Order By: Relevance
“…In support of epidemiological data, analysis of 976 colonoscopies showed that T2D patients exhibit a higher incidence of polyps and higher-grade dysplasia/ carcinoma (even higher in uncontrolled diabetes) when compared to nondiabetic patients (Miłek et al 2019). Although T2D is associated to higher grade CRC, it has not been associated to particular molecular subtypes of CRC (CMS) as summarized (Gutiérrez-Salmerón et al 2021). However, clinical adoption of CMS-based classification (integrating biological layers) to guide CRC prognosis and treatment is hampered by practical obstacles such as the influence of where the tumour samples are taken, availability of bioinformatic procedures, and the need for clinical trials to confirm their predictive value for therapy response (Buikhuisen et al 2020).…”
Section: Introductionmentioning
confidence: 85%
See 3 more Smart Citations
“…In support of epidemiological data, analysis of 976 colonoscopies showed that T2D patients exhibit a higher incidence of polyps and higher-grade dysplasia/ carcinoma (even higher in uncontrolled diabetes) when compared to nondiabetic patients (Miłek et al 2019). Although T2D is associated to higher grade CRC, it has not been associated to particular molecular subtypes of CRC (CMS) as summarized (Gutiérrez-Salmerón et al 2021). However, clinical adoption of CMS-based classification (integrating biological layers) to guide CRC prognosis and treatment is hampered by practical obstacles such as the influence of where the tumour samples are taken, availability of bioinformatic procedures, and the need for clinical trials to confirm their predictive value for therapy response (Buikhuisen et al 2020).…”
Section: Introductionmentioning
confidence: 85%
“…However, most MAIT cells are recruited after the tumour is formed making it unlikely that MAIT-dependent inflammation initiates sporadic CRC. The localized inflammatory tumour microenvironment, with increased ROS that favour mutations and epigenetic changes, may lead to tumour progression (Gutiérrez-Salmerón et al 2021). Cytokines produced inside the tumour, mainly by TILs (IL17) and TAMs (TNFA, IL6, TGFB, IL10, VEFG) and outside the tumour (in blood and/or neighbouring WAT) in T2D patients, may have an adjuvant effect on tumour progression (Landskron et al 2014) (Fig.…”
Section: Inflammation Cooperates With Metabolism To Remodel Tumour Infiltration In Crcmentioning
confidence: 99%
See 2 more Smart Citations
“…Beim kolorektalen Karzinom steigt die Leptinexpression von der normalen Kolonmukosa über das Adenom zum Adenokarzinom stark an, was darauf schließen lässt, dass es in die Mehrschrittkarzinogenese involviert ist. Aus translationalen Studien wird deutlich, dass Leptin direkt mit einem erhöhten Risiko, an einem kolorektalen Karzinom zu erkranken, und einem aggressiveren Phänotyp korreliert ist, wie Daten zu einem verminderten remissionsfreien Überleben zeigen [26].…”
Section: Fettgewebe Und Chronische Niedriggradige Entzündungunclassified